Showing the Unspeakable: China Daily's Pictures of Donald Trump and the United States of America - Koleva, Vanya (My University, 2023)
This study aims at analyzing cartoons of Donald Trump to shed light on nuances of U.S.-China relations and China’s view of the democratic process in the United States. Fifty-nine cartoons that depict Donald Trump were selected from China Daily’s website from September 2016 to July 2020 and were examined through semiotic analysis. The results suggest a deterioration in U.S.-China relations during the trade war that started in 2018, which is depicted as damaging to the U.S. and the world but not to China. Donald Trump is illustrated as ignorant and aggressive, therefore dangerous while the democratic process is suggested to be failing and redundant. These representations allow for China to implicitly boost its image on the international stage. In the period from September 2018 to April 2020 only one cartoon of Donald Trump in China Daily’s website was found, while from April to July 2020, Trump’s face was hidden in most cartoons. The study suggest the reason is Trump’s loss of China’s respect.
Keywords: political cartoons, Donald Trump, US-China relations